PERAN KEGIATAN GREEN LAB DALAM MENINGKATKAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR ALAM - Mutik Nur Fadhilah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
The Merdeka Belajar curriculum is identical to project-based learning. This learning is implemented in the Pancasila Student Profile Strengthening Project (P5) activities. Therefore, schools are required to have a program for the implementation of the P5. This study aimed to determine the implementation and role of Green Lab activities in increasing the profile of Pancasila students. The research method used is qualitative with a descriptive approach. The data collection was obtained through observation, interviews, and documentation. The subjects of this study were students at SD Sekolah Alam Excellentia. The study results indicate that implementing the Green Lab follows the syntax in the parent's book, which consists of praying, planting seeds, watering, giving fertilizer, planting together in the garden, sweeping, taking out the garbage, queuing, and feeding animals. The role of Green Lab activities in increasing the profile of Pancasila students, namely: habituation of noble character (pray) and love for the surrounding environment, tolerance in queuing activities by prioritizing common interests over individual interests, collaboration in sweeping and disposing of garbage, trained independence in watering plants, accustomed to solving problems, able to produce a masterpiece in decorating the pot. The impact is to strengthen the profile of Pancasila students from an early age. In the future, they will become superior individuals.